Independently tunable multichannel terahertz filters - 张会云 高营 张玉萍 王世范 (Chinese physics B, 2011)
We numerically demonstrate terahertz multichannel filters with independently tunable defect modes based on fractal photonic crystMs. Single defect and multiple defects models are proposed to fabricate the multichannel terahertz filters. The facts that the wave functions of the defect states do not overlap and their bases are orthogonal lead to the independency among the defect modes. The simulated results theoretically provide the principle for fabricating independently tunable multichannel terahertz filters by utilizing one-dimensional phot（~nic crystals with defects.